Copper oxide nanoparticles alter cellular morphology via disturbing the actin cytoskeleton dynamics in Arabidopsis roots. Issue 1 (2nd January 2020) - Jia, Honglei; Chen, Sisi; Wang, Xiaofeng; Shi, Cong; Liu, Kena; Zhang, Shuangxi; Li, Jisheng
Abstract: Copper oxide nanoparticles (CuO NPs) have severe nano-toxic effects on organisms. Limited data is available on influence of CuO NPs on plant cells. Here, the molecular mechanisms involved in the toxicity of CuO NPs are studied. Exposure to CuO NPs significantly increased copper content in roots (0.062–0.325 mg/g FW), but CuO NPs translocation rates from root to shoot were low (1.1–2.8%). Presented data were significant at p  < 0.05 compared to control. CuO NPs inhibited longitudinal growth and promoted transverse growth in root tip cells. However, CuO NPs did not affect the leaf cells, implying that the transfer ability of CuO NPs was weak, and toxicity mainly affected roots. CuO NPs can conjugate with actin protein. The actin cytoskeleton experienced reorganization in the presence of CuO NPs. The longitudinal filamentous actin (F-actin) decreased, and the transverse F-actin increased. CuO NPs inhibited actin polymerization and promoted depolymerization. The behavior of individual F-actin was at steady state with time-lapse under CuO NPs treatment by time-lapse reflection fluorescence (TIRF) microscopy. The growth rate of actin filaments was weakened by CuO NPs. CuO NPs disturbed the subcellular localization of PINs and the gradient of auxin distribution in root tips in an actin-dependent manner. In conclusion, CuO NPs conjugated with actin and disturbed F-actin dynamics, triggering abnormal cell growth in the root tip, and findings provide theoretical basis for further study nano-toxicity in plants.